2005
DOI: 10.1111/j.1742-4658.2005.04991.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and sequence identification of anserinase

Abstract: Anserinase (Xaa‐methyl‐His dipeptidase, EC 3.4.13.5) is a dipeptidase that mainly catalyzes the hydrolysis of Nα‐acetylhistidine in the brain, retina and vitreous body of all poikilothermic vertebrates. The gene encoding anserinase has not been previously identified. We report the molecular identification of anserinase, purified from brain of Nile tilapia Oreochromis niloticus. The determination of the N‐terminal sequence of the purified anserinase allowed the design of primers permitting the corresponding cDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Other predictive transcripts are indicative of an oxidative stress response in polluted environments, including an aldo-keto reductase and copper/zinc superoxide dismutase. The glutamate carboxypeptidase-like clone, which is associated with folate and homocysteine levels and is similar to anserinase (Yamada et al, 2005) also contributed to prediction, warranting further study on its function and regulation. The well documented biomarkers CYP1A, choriogenin and metallothionein were also strong predictors.…”
Section: Class Predictionmentioning
confidence: 97%
“…Other predictive transcripts are indicative of an oxidative stress response in polluted environments, including an aldo-keto reductase and copper/zinc superoxide dismutase. The glutamate carboxypeptidase-like clone, which is associated with folate and homocysteine levels and is similar to anserinase (Yamada et al, 2005) also contributed to prediction, warranting further study on its function and regulation. The well documented biomarkers CYP1A, choriogenin and metallothionein were also strong predictors.…”
Section: Class Predictionmentioning
confidence: 97%
“…It was named anserinase because it was first described in codling muscle (203), which uniquely contains anserine as HCD. Yamada et al (394) recently identified anserinase molecularly and proposed a phylogenetic tree with three separate families of carnosinase-like enzymes, being serum carnosinase like (CN1), cytosolic nonspecific dipeptidaselike (CN2), and anserinase-like. Other carnosinases have been described within the EC 3.4.13 family of dipeptidases, but their enzyme classification (such as EC 3.4.13.3) is now deleted because its activity is covered by CN1 and CN2.…”
Section: Other Dipeptidases With Carnosinase Activitymentioning
confidence: 99%
“…3h). These catabolic enzymes and their anserine/carnosine substrates have been associated with cognitive functioning, neurovascular activity and physiological homeostasis of histidine-containing dipeptides [45][46][47] . This further supports the specific activity of OXT in homeostatic regulation of tilapia's metabolic response to cold stress.…”
Section: Oxt Signaling Reduces Metabolism In Poikilotherms Under Extreme Cold Conditionsmentioning
confidence: 99%